Decolorization and biodegradation of Mordant Orange-1 by newly isolated trichoderma harzianum RY 36 and acremonium spinosum RY 42 [electronic resource] - Rubiyatno, 1988- author; Tony Hadibarata; Fakulti Kejuruteraan Awam (2014)
Thesis (Sarjana Kejuruteraan (Awam - Alam Sekitar))) - Universiti Teknologi Malaysia, 2014